Neurodegeneration in a Drosophila model of adrenoleukodystrophy: the roles of the Bubblegum and Double bubble acyl-CoA synthetases - Anna Sivachenko; Hannah B. Gordon; Suzanne S. Kimball; Erin J. Gavin; Joshua L. Bonkowsky; Anthea Letsou (The Company of Biologists, 2016)
Debilitating neurodegenerative conditions with metabolic origins affect millions of individuals worldwide. Still, for most of these neurometabolic disorders there are neither cures nor disease-modifying therapies, and novel animal models are needed for elucidation of disease pathology and identification of potential therapeutic agents. To date, metabolic neurodegenerative disease has been modeled in animals with only limited success, in part because existing models constitute analyses of single mutants and have thus overlooked potential redundancy within metabolic gene pathways associated with disease. Here, we present the first analysis of a very-long-chain acyl-CoA synthetase (ACS) double mutant. We show that the Drosophila bubblegum (bgm) and double bubble (dbb) genes have overlapping functions, and that the consequences of double knockout of both bubblegum and double bubble in the fly brain are profound, affecting behavior and brain morphology, and providing the best paradigm to date for an animal model of adrenoleukodystrophy (ALD), a fatal childhood neurodegenerative disease associated with the accumulation of very-long-chain fatty acids. Using this more fully penetrant model of disease to interrogate brain morphology at the level of electron microscopy, we show that dysregulation of fatty acid metabolism via disruption of ACS function in vivo is causal of neurodegenerative pathologies that are evident in both neuronal cells and their supporting cell populations, and leads ultimately to lytic cell death in affected areas of the brain. Finally, in an extension of our model system to the study of human disease, we describe our identification of an individual with leukodystrophy who harbors a rare mutation in SLC27a6 (encoding a very-long-chain ACS), a human homolog of bgm and dbb.